URGENSI PENDIDIKAN KEWARGANEGARAAN DALAM PEMBENTUKAN KARAKTER DI SEKOLAH DASAR - Sudirman, I Nyoman; Lidia Yanti, Ni Wayan; Putri Mahayani, Ni Wayan; Yulistyarini, Ni Luh Made; Nopianti, Ni Komang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The decline in national character amid globalization has become a major challenge that requires serious attention, particularly through the education sector. Elementary school serves as a strategic stage for instilling character values because children are in a crucial period of moral and personality development. Civic Education plays a significant role in developing students into responsible citizens with strong moral values based on Pancasila. This study aims to examine the contribution of Civic Education to the development of national character in elementary schools. The study employed a literature review method by collecting and analyzing relevant references from scientific journals, books, conference proceedings, and official documents related to Civic Education and character education. The findings indicate that Civic Education contributes significantly to character building by integrating Pancasila values into the learning process, fostering positive habits, and providing exemplary behavior through teachers and the school environment. Civic Education also promotes essential character values, including honesty, discipline, responsibility, tolerance, cooperation, and patriotism. Furthermore, character development is strengthened through classroom learning, co-curricular and extracurricular activities, as well as the implementation of a positive school culture. Therefore, Civic Education is not only intended to provide knowledge about citizenship but also functions as an effective instrument for shaping students' character from an early age. Strengthening Civic Education in elementary schools is expected to produce a generation that possesses noble character, social responsibility, democratic attitudes, and a strong commitment to national values.